A novel system for the improvement of colonic cleansing during colonoscopy - Rigaux, J.; Juriens, I.; Devière, J. (Endoscopy, 2012)
Suboptimal bowel cleansing prior to colonoscopy impairs the efficacy and safety of the procedure. A new system for intracolonic cleansing has been developed, which includes a disposable catheter device that is inserted through the working channel of a standard colonoscope and an irrigation unit with predefined pressure and flow rate. The aim of the current study was to assess the safety and efficacy of this novel system for the improvement of bowel cleansing during colonoscopy. A total of 42 patients with suboptimal bowel preparation were systematically allocated, in a 1:1 ratio, to either the study group (JetPrep system, n = 21) or the control group (syringe irrigation, n = 21). The cleansing efficacy was evaluated using a segmental scoring scale to rate the bowel preparation level before and after irrigation. One patient from the study group was excluded from the efficacy analysis due to treatment with both techniques. The JetPrep system was significantly superior to syringe irrigation (P = 0.0001). No adverse events were reported. This study suggests that the safety profile of the JetPrep system is comparable to standard irrigation and shows that the device significantly improves suboptimal bowel preparation.